Mapping Art: 3D geo-visualization and virtual worlds in cultural heritage - George Malaperdas; Aggeliki Barberopoulou (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2023)
The purpose of this paper is to highlight the use of digital mapping and GIS in combination with 3D geo-visualization in depicting landscapes and cultural heritage sites. As computers evolve in their processing capabilities (graphics card, processor, memory speed), so does the graphical output representing our world that can be done in less time. Short processing times and available highly sophisticated software create conditions to test existing models of our 3D world or best create alternative renderings of monuments and landscapes. A study area has been chosen to present such a methodology. Ancient Pylos was selected as the study area due to the abundance of bibliographic references available, facilitating the creation of a cartographic representation of the region based on archaeological discoveries and historical sources. The advantages of employing 3D geo-visualizations in archaeology are numerous and are examined within this article. Visual imaging aids archaeologists in elucidating intricate or deficient details pertaining to a monument, simultaneously streamlining archaeological data for easier comprehension by the general public. The use of 3D geo-visualization to represent data and other non-photorealistic details is expected to dominate in the near future.